The patient with endocrine disease. Issue 12 (December 2019) - Wood, Madeleine; Welch, Sarah
Abstract: Uncontrolled endocrine pathology can cause significant adverse complications during a patient's perioperative journey. With the ageing population, increasing comorbidity and rising obesity rates, the incidence of endocrine disease in elective and emergency work is likely to increase. A thorough understanding of diagnosis and management perioperatively is essential to prevent any excess morbidity and mortality. The perioperative period may precipitate endocrine emergencies which require rapid diagnosis and life-saving treatments. This article will cover the management of diabetes, thyroid and adrenal disease in the perioperative period.